RANCANGAN USAHA AGRIBISNIS TANAMAN SAYURAN BERBASIS HIDROPONIK - Asriani Asriani; Dhian Herdhiansyah; Nurcayah Nurcayah (Universitas Galuh, 2022)
The government's program on food security needs to get support through the application of appropriate technology in the agricultural sector. Hydroponics is an agricultural vegetable cultivation technology that needs to be developed in an effort to increase vegetable production and encourage the development of agribusiness entrepreneurship. The purpose of this research is the development of hydroponic plant cultivation technology through the Nutrient Film Technique (NFT) system and the Wick system. The method used is a qualitative method in the form of an applicative application of hydroponic cultivation. The results of the research are in the form of installation designs and hydroponic cultivation techniques that can be developed into teaching materials and new entrepreneurs in the field of agriculture.